การวิเคราะห์ผลได้ ด้นทุน และจุดคุ้มทุน ของการผลิตน้ำมันไบโอดีเซล ด้วยกรดไขมันปาล์ม - มากเจริญ ลำใย (RMUTP Research Journal Sciences and Technology, 2014)
บทคัดย่อ งานวิจัยครั้งนี้ทำการวิเคราะห์ผลได้ ต้นทุน จุดคุ้มทุน รวมถึงการวิเคราะห์ความอ่อนไหวจากการ ลงทุนสร้างโรงงานผลิตนํ้ามันไบโอดีเซลจากกรดไขมันปาล์ม การศึกษาครั้งนี้จะใช้ข้อมูลจากระบบการผลิตไบโอดีเซลของสถาบันวิจัยวิทยาศาสตร์และเทคโนโลยีแห่งประเทศไทยเป็นต้นแบบ จากการศึกษาพบว่า โครงการนี้มีมูลค่าปัจจุบันสุทธิติดลบ 27,024,966 บาท และเมื่อนำมาวิเคราะห์ความอ่อนไหวของโครงการโดยให้ราคาไบโอดีเซลเพิ่มขึ้น 5% และ 7.5% แต่ให้ราคาวัตถุดิบลดลง 10% และ 20% พบว่าทุกกรณีมีมูลค่า ปัจจุบันสุทธิติดลบ หากต้องการคืนทุนที่อายุโครงการ 5 ปี 8 ปี และ 10 ปีนั้นที่ราคาใบโอดีเซลลิตรละ 31.71 บาท ต้นทุนกรดไขบันปาล์มจะต้องต่ำกว่า 2.89 3.05 และ 3.82 บาทต่อกิโลกรม ตามลำดับ แต่ถ้าราคาไบโอดีเซล ลิตรละ 33.30 บาท จะต้องมีต้นทุนกรดไขบันปาล์มตากว่า 4.65 4.82 และ 5.58 บาทต่อกิโลกรม ตามลำดับ Abstract The research analyzes benefit, cost and break even point including sensitivity of making biodiesel production factory from palm fatty acid. Biodiesel production system of Thailand Institute of Scientific and Technological Research (TISTR) is used for this study. It is found the present net value has been a deficit of 27,024,966 baht. The sensitivity of the project has been analyzed by increasing selling price of biodiesel of 5% and 7.5%, but reducing material price of 10% and 20%. It is found the present net value still has been deficient. The project will payback at 5th, 8th and 10th year be with selling price of biodiesel, is about 31.71 baht per litre. Therefore, the cost of palm fatty acid should lower than 2.89, 3.05 and 3.82 baht per kilogram. If selling price of biodiesel about 33.30 baht per litre, the cost of palm fatty acid should be lower than 4.65, 4.82 and 5.58 baht per kilogram, respectively.